Challenges and Pitfalls for Implementing Digital Health Solutions in Clinical Studies in Europe - Meyerheim, Marcel; Burns-Gebhart, Anna; Mirzaie, Kasra; Garani-Papadatos, Tina; Braun, Yvonne; Graf, Norbert (Frontiers in Digital Health, 2021)
- The increasing number of digital solutions developed for use in clinical health care settings is accompanied by new challenges to develop and conduct clinical studies that include eHealth technologies. - Clinical study implementation plans often disregard or underestimate the necessity of additional administrative and logistic tasks required at clinical sites as well as ethical aspects to test digital solutions. - Experiences made in the run-up of an observational clinical feasibility study at three international clinical sites in the framework of the MyPal project (https://mypal-project.eu/) result in recommendations to avoid delays and barriers in the planning of such prospective studies in clinical and also palliative care for increased efficiency.